Novel genotype–phenotype associations demonstrated by high-throughput sequencing in patients with hypertrophic cardiomyopathy. Issue 4 (28th October 2014) - Lopes, Luis R; Syrris, Petros; Guttmann, Oliver P; O'Mahony, Constantinos; Tang, Hak Chiaw; Dalageorgou, Chrysoula; Jenkins, Sharon; Hubank, Mike; Monserrat, Lorenzo; McKenna, William J; Plagnol, Vincent; Elliott, Perry M
Abstract : Objective: A predictable relation between genotype and disease expression is needed in order to use genetic testing for clinical decision-making in hypertrophic cardiomyopathy (HCM). The primary aims of this study were to examine the phenotypes associated with sarcomere protein (SP) gene mutations and test the hypothesis that variation in non-sarcomere genes modifies the phenotype. Methods: Unrelated and consecutive patients were clinically evaluated and prospectively followed in a specialist clinic. High-throughput sequencing was used to analyse 41 genes implicated in inherited cardiac conditions. Variants in SP and non-SP genes were tested for associations with phenotype and survival. Results: 874 patients (49.6±15.4 years, 67.8% men) were studied; likely disease-causing SP gene variants were detected in 383 (43.8%). Patients with SP variants were characterised by younger age and higher prevalence of family history of HCM, family history of sudden cardiac death, asymmetric septal hypertrophy, greater maximum LV wall thickness (all p values<0.0005) and an increased incidence of cardiovascular death (p=0.012). Similar associations were observed for individual SP genes. Patients with ANK2 variants had greater maximum wall thickness (p=0.0005). Associations at a lower level of significance were demonstrated with variation in other non-SP genes. Conclusions: Patients with HCM caused by rare SP variants differ with respect to age at presentation, family history of the disease, morphology and survival from patients without SP variants. Novel associations for SP genes are reported and, for the first time, we demonstrate possible influence of variation in non-SP genes associated with other forms of cardiomyopathy and arrhythmia syndromes on the clinical phenotype of HCM.